Why are some genetic diseases common? Distinguishing selection from other processes by molecular analysis of globin gene variants. - Flint, J; Harding, R; Clegg, J; Boyce, A (Springer-Verlag, 1993)
Various processes (selection, mutation, migration and genetic drift) are known to determine the frequency of genetic disease in human populations, but so far it has proved almost impossible to decide to what extent each is responsible for the presence of a particular genetic disease. The techniques of gene and haplotype analysis offer new hope in addressing this issue, and we review relevant studies of three haemoglobinopathies: sickle cell anaemia, and alpha and beta thalassaemia. We show how for each disease it is possible to recognize a pattern of regionally specific mutations, found in association with one or a few haplotypes, that is best explained as the result of selection; other patterns are due to population migration and genetic drift. However, we caution that such conclusions can be drawn in special circumstances only. In the case of the haemoglobinopathies it is possible because a selective agent (malaria) was already suspected, and the investigations could be carried out in relatively genetically homogenous populations whose migratory histories are known. Moreover, some data reviewed here suggest that gene conversion and the haplotype composition of a population may affect the frequency of a mutation, making interpretation of gene frequencies difficult on the basis of standard population genetics theory. Hence attempts to use the same approaches with other genetic diseases are likely to be frustrated by a lack of suitably untrammelled populations and by difficulties accounting for poorly understood genetic processes. We conclude that although this combination of molecular and population genetics is successful when applied to the study of haemoglobinopathies, it may not be so easy to apply it to the study of other genetic diseases.